Resourcefulness Development in Entrepreneurship Program to Improve Resilience of Disabled Students At “Yakut” Special School Type C-C1 Purwokerto - Alief Budiyono (Indonesian Academy of Social and Religious Research (IASRR), 2022)
Children with special needs or special health care needs (e.g., Down syndrome (DS), autism spectrum disorder (ASD), and cerebral palsy (CP)) are considered special because they require, in most cases, extraordinary long-term care in the hope of meeting developmental needs. In this regard, there is a systemic perspective of resilience in the ecology and development context, pursuing to identify for individuals to cope with persistent stresses. Based on this problem, “YAKUT” Special School type C-CI Purwokerto conducted a resourcefulness development program for mentally disabled students at “YAKUT” Special School type C-CI Purwokerto to increase the resilience of these students. In this study, the researcher used a qualitative type of research. The data collection process was carried out through observations at Yakut” Special School type C-CI Purwokerto, held from November to December 2021, and interviews with teachers at “YAKUT” Special School type C-CI. The entrepreneurial program programmed by “YAKUT” Special School type C-CI Purwokerto aims to help students remain competitive in the community. Students are trained to be tough and adapt to their limitations in this situation. Students who have resilience are willing to work hard to achieve their goals, adapt to changes to take advantage of new situations, and learn from their mistakes.